Connecting Science and Engineering Education Practices in Meaningful Ways Building Bridges - Annetta, Leonard A.; Minogue, James (Contemporary Trends and Issues in Science Education, 2016)
The need for a scientifically literate citizenry, one that is able to think critically and engage productively in the engineering design process, has never been greater. By raising engineering design to the same level as scientific inquiry the Next Generation Science Standards' (NGSS) have signaled their commitment to the integration of engineering design into the fabric of science education. This call has raised many critical questions...How well do these new standards represent what actually engineers do? Where do the deep connections among science and engineering practices lie? To what extent can (or even should) science and engineering practices co-exist in formal and informal educational spaces? Which of the core science concepts are best to leverage in the pursuit of coherent and compelling integration of engineering practices? What science important content may be pushed aside? This book, tackles many of these tough questions head on. All of the contributing authors consider the same core question: Given the rapidly changing landscape of science education, including the elevated status of engineering design, what are the best approaches to the effective integration of the science and engineering practices? They answered with rich descriptions of pioneering approaches, critical insights, and useful practical examples of how embodying a culture of interdisciplinarity and innovation can fuel the development of a scientifically li terate citizenry. This collection of work builds traversable bridges across diverse research communities and begins to break down long standing disciplinary silos that have historically often hamstrung well-meaning efforts to bring research and practice from science and engineering together in meaningful and lasting ways.